2018
DOI: 10.1080/09571736.2018.1503139
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of different explicit vocabulary-teaching strategies on learners’ retention of technical and academic words

Abstract: The effectiveness of different explicit vocabulary teaching strategies on learners' retention of technical and academic words The effectiveness of explicit instruction, within the context of strategy development in learners, has been widely accepted for several years. However, the methods used within explicit vocabulary instruction are varied and comparatively few studies have directly compared methods. This study investigates the type of instruction (in a visual or written context) as well as the timing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…By comparing this two theories, Sadoski, Goetz, and Avila concluded that their results were more consistent with the dual coding theory. The results of previous research [11] also showed that pre-teaching with visual aids has a positive effect on vocabulary acquisition compared with pre-teaching with only written context. They believe that this multi-modal approach improves learners' ability to pay attention to vocabulary items and thus increase their vocabulary learning.…”
Section: Vocabulary Learning and Dual Codementioning
confidence: 80%
“…By comparing this two theories, Sadoski, Goetz, and Avila concluded that their results were more consistent with the dual coding theory. The results of previous research [11] also showed that pre-teaching with visual aids has a positive effect on vocabulary acquisition compared with pre-teaching with only written context. They believe that this multi-modal approach improves learners' ability to pay attention to vocabulary items and thus increase their vocabulary learning.…”
Section: Vocabulary Learning and Dual Codementioning
confidence: 80%
“…In their study on explicit vocabulary instruction, Nash and Snowling (2006) revealed that learners' vocabulary knowledge is greatly enhanced by using a contextual approach to the instruction as compared to merely emphasizing word definitions. Many research have shown the importance of providing direct guidance in teaching vocabulary via different techniques and strategies (Alamri & Rogers, 2018;Hennerbry et al, 2017;Huffman, 2010;Norris & Ortega, 2000;Oxford, 2003;Read, 2004). However, to the researcher's knowledge, most of these research mainly employed quantitative means in measuring the development of vocabulary knowledge achieved by learners.…”
Section: Student Collaboration In Vocabulary Acquisitionmentioning
confidence: 99%
“…There have been several attempts to foster knowledge of academic vocabulary (Alamri & Rogers, 2018;Horst, Cobb, & Nicolae, 2005;Scammacca & Stillman, 2018;Thurston & Candlin, 1998). One way to help ESL students recall the meanings of academic words and less known expressions is to offer them access to a web-based platform where they can acquire knowledge of these lexical items and participate in a series of interactive activities that help in the productive use of the recently acquired vocabulary (Horst et al, 2005).…”
Section: Overview Of Academic Vocabularymentioning
confidence: 99%
“…Opinions gleaned from the students indicated that exposure to this type of vocabulary instruction is conducive to better retention of academic lexis. Alamri and Rogers (2018) tested several explicit ways of teaching technical and academic vocabulary and concluded that pre-instructional exposure to domain-specific terms with the help of a visual aid had a positive impact on the learning of academic vocabulary. Repeated exposure to subject-matter vocabulary is investigated by Scammacca and Stillman (2018) who noticed that allowing low-level students the opportunity to read texts several times made them aware of a wide range of vocabulary in the domain of social studies.…”
Section: Overview Of Academic Vocabularymentioning
confidence: 99%